The beautiful short story. "Viator", by Juan Benet - Sullà, Enric (Tropelías: Review of Literary Theory and Comparative Literature, 1997)
The beautiful short story, "Viator", by Juan Benet, is used both as an object for a sustained close reading, which draws on liberally on current narratological concepts, and as, mainly, for an interpretation procedure, i.e., the assignmenl of meaning. If the reading section drells on description and verification of textual data, interpretation intends to go further and throw some light on the multiple meanings allowed by the negotiation between text and reader. To the always impending refusal to interpret, it is argued exactly the opposite attitude: the pleasure of interpreting, of giving meaning to texts, resisting however the templation to privilege one over another, notwithstanding the fact that there always are academic borders that would push a hypothetic reader to assign the text a definite meaning.
Keywords: Juan Benet; interpretation